DEVELOPMENT OF SCHOOLOGY BASED ELECTRONIC LEARNING MEDIA IN PLANT AND ANIMAL TISSUE STRUCTURE MATERIALS - Cleneagles Theresia; Nurmasari Sartono; Ratna Dewi Wulaningsih (Fakultas MIPA Universitas Negeri Gorontalo, 2021)
21st-century learning has brought out innovations in the field of education, such as learning that is no longer only done in the classroom or virtual classes with digital learning media that no longer use text alone but include audio, video, and the internet in learning. However, the development of learning media that links technology has not been optimal. Educators still have not linked videos or representative images to Biology learning, especially plant tissue and animal tissue material, so it is found that students have not mastered these materials well. This study aims to produce e-learning media that can be supported through one type of LMS (Learning Management System) application, namely Schoology, which is valid and effective on plant and animal tissue material. This research was conducted using the ADDIE model, starting from the analysis, design, development, implementation, and evaluation stages. The products developed by experts validated by 74% are in good categories, as well as the feasibility test of teachers and students who get a score of 89.60% with a very good category. The development product proved to be effective in high school learning with an increase in learning outcomes using the N-Gain test of 0.54 on plant tissue material and 0.52 on animal tissue material with moderate criteria.